2004
DOI: 10.3409/1734916044527502
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of the chicken embryo model for assessment of biological activity of different oligosaccharides

Abstract: The effect of different oligosaccharides-"-galactoside preparations from Lupinus albus seeds differing in sucrose content, raffinose and fructooligosaccharides on the growth of chicken intestine microflora and the hatchability and weight of the treated embryos were studied. The assessment of biological activity of these oligosaccharides was done in ovo on the chicken embryo model. The eggs of experimental groups containing twelve days old embryos were injected into the air cell with 0.2 ml of Ringer water solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
56
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 23 publications
2
56
0
Order By: Relevance
“…Casas‐Perez and Edens found that the administration of probiotics (lactic acid bacteria) via the in ovo technique, should be done on the 18th day of incubation. In ovo injection of some oligosaccharides on the 12th day of incubation is a preferable time that could improve growth performance, nutrient digestibility and feed efficiency, development of the immune system, and meat quality . The in ovo chicken transfection technique using ethylenediaminetetraacetic acid complemented with lipoplexes has also been evaluated to develop a puncture‐free method of producing transgenic chicks .…”
Section: Basics Of In Ovo Technologymentioning
confidence: 99%
“…Casas‐Perez and Edens found that the administration of probiotics (lactic acid bacteria) via the in ovo technique, should be done on the 18th day of incubation. In ovo injection of some oligosaccharides on the 12th day of incubation is a preferable time that could improve growth performance, nutrient digestibility and feed efficiency, development of the immune system, and meat quality . The in ovo chicken transfection technique using ethylenediaminetetraacetic acid complemented with lipoplexes has also been evaluated to develop a puncture‐free method of producing transgenic chicks .…”
Section: Basics Of In Ovo Technologymentioning
confidence: 99%
“…It has been noted that the colonization of GIT with nonpathogenic microorganisms creates a protective surface against pathogens (Mahroop Ra, Raja, & Mohamed Im, ). In ovo administration of probiotic bacteria may lead to GIT colonization before the first contact with environmental microorganisms (Villaluenga, Wardeńska, Pilarski, Bednarczyk, & Gulewicz, ). The initial microbe inoculation may protect the gut of the chick from pathogenic bacteria by competitive exclusion mechanisms, which are based on bacterial interactions mediated by competition for mucosal adhesion sites and nutrients (Majidzadeh Heravi et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Substances administered in ovo during the embryonic development of birds reach the intestines and affect the development of the gastrointestinal tract before hatching. Villaluenga et al [16] demonstrated that the optimal time for the injection of a prebiotic is the 12 th day of embryonic development. In comparison with injections on d 1, 8 and 17, a significantly higher number of bifidobacteria was observed in the gut.…”
Section: Introductionmentioning
confidence: 99%